Molecular cloning and expression of cDNA encoding a lumenal calcium binding glycoprotein from sarcoplasmic reticulum. - Leberer, E (1989)
Antibody screening was used to isolate a cDNA encoding the 160-kDa glycoprotein of rabbit skeletal muscle sarcoplasmic reticulum. The cDNA is identical to that encoding the 53-kDa glycoprotein except that it contains an in-frame insertion of 1308 nucleotides near its 5' end, apparently resulting from alternative splicing. The protein encoded by the cDNA would contain a 19-residue NH2-terminal signal sequence and a 453-residue COOH-terminal sequence identical to the 53-kDa glycoprotein. It would also contain a 436-amino acid insert between these sequences. This insert would be highly acidic, suggesting that it might bind Ca2+. The purified 160-kDa glycoprotein and the glycoprotein expressed in COS-1 cells transfected with cDNA encoding the 160-kDa glycoprotein were shown to bind 45Ca2+ in a gel overlay assay. The protein was shown to be located in the lumen of the sarcoplasmic reticulum and to be associated through Ca2+ with the membrane. We propose that this lumenal Ca2+ binding glycoprotein of the sarcoplasmic reticulum be designated "sarcalumenin."